THE INFLUENCE OF EXTERNAL ENVIRONMENTAL STRENGTHS AND COMPANY RESOURCES ON COMPANY PERFORMANCE WITH COMPETITIVE STRATEGIES AS AN INTERVENING VARIABLE ON CATERING SERVICES PT HANAN BOGA RASA IN WEST JAVA - Mariana Rachmawati; Wandi Kurniad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
One part of the food and beverage industry is the catering industry. Where in it there is a catering service business. The catering service business is currently very much in demand by many people, because of the increasing mobility of life in this city, there are many requests from people who need these services. Because at this time most of them think practically, when holding an event that requires food and beverage services, from there catering services have now become one of the needs of the metropolitan community and because of that the growth of the catering industry is growing rapidly, many entrepreneurs are taking advantage of this opportunity. The analysis unit and the observation / observation unit used as the object in this study are "The Influence of External Environmental Strengths and Company Resources on Company Performance with Competitive Strategies as an Intervening Variable in Cathering Services PT. Hanan Boga Rasa in West Java. The external environmental forces with KLE2 (macro force: political turmoil) as its most influential factor, give the strongest impact on competitive strategy than the company resources, though both variables affected competitive strategy. Meanwhile, the company resources with SDP9 (intangible assets: quality level of experts) as its most influential factor, influences the company performance more than the external environmental forces do. In addition, competitive strategy with SB8 (speed-based strategy: speed movement in anticipating the latest technology trends) as its most influential factor, affects the company performance. The main elements offered differentiate between PT. Hanan Boga Rasa and other catering businesses are Variative product differentiation, High quality food products, Good chef, Excellent customer service. unique marketing method, Strategic location. The initial stage of this business plan is to have a strategic location, but the long-term target is to have branches in Kota and Kota Regencies.